W. E. B. Du Bois: American prophet - Blum, Edward J. (Politics and culture in modern America, 2009)
W. E. B. Du Bois, American Prophet is the first religious biography of this leading civil rights activist and intellectual. Though Du Bois is often labeled an atheist, historian Edward J. Blum argues that his religious and spiritual insights are central to understanding his political and intellectual work.